Investment, subsidies, and pro-poor growth in rural India - Fan, Shenggen; Gulati, Ashok; Thorat, Sukhadeo (Wiley, 2008)
This article reviews the trends in government subsidies and investments in and for Indian agriculture; develops a conceptual framework and a model to assess the impact of various subsidies and investments on agricultural growth and poverty reduction; and presents reform options with regard to re‐prioritizing government spending. Subsidies in credit, fertilizer, and irrigation have been crucial for small farmers to adopt new technologies particularly during the initial stage of the green revolution in the late 1960s and 1970s. But it is now investments in agricultural research, education, and rural roads that are the three most effective public spending items in promoting agricultural growth and reducing poverty.